Production of Glucose Syrup Derived from Cassava Peel Starch Using Amylase Enzyme from Green Bean Seed Sprout Extract (Phaseolus radiatus L.) - Emma Zaidar Nasution; Sari Mutiara Ginting (Talenta Publisher, 2024)
The production of glucose syrup derived from cassava peels starch using amylase enzyme from green bean seed sprout extract (Phaseolus radiatus L.) has been carried out by isolating the enzyme from the green bean seed sprouts extract then purified by precipitation using ammonium sulphate with the saturation of 60% (w/v). Amylase enzyme activity was determined using the Nelson Somogyi method. The research results obtained the activity of the amylase enzyme in the deposition of 60% ammonium sulphate at 12.22 U/mL. Amylase enzyme was applied as a hydrolyzed starch from cassava peels with a weight ratio of raw material with water 10% (w / v) to produce glucose syrup with the addition of 0.25% enzyme; 0.5%; 0.75%; 1% (v / v). The glucose syrup obtained was then tested for viscosity, reducing sugars, water content, ash content, and organoleptics. The best glucose syrup analysis results from adding 1% amylase enzyme with a viscosity value of 238.71cP, water content of 12.45%, reduction sugar content of 33.81%, ash content of 0.49%, and dextrose equivalent value of 50.16%.